4 in 1 safety kit / Nur Maisarah Afiqah Mazlan ... [et al.] - Mazlan, Nur Maisarah Afiqah; Afandi, Aina Afriena; A.Lukman, Aida Najihah; Mazlan, Muhammad Irfan; Mohd Zaidi, Nur Murniza (2021)
Numerous of us have that on-edge feeling which runs through our bodies on a regular basis especially when we are alone. In reality, we do not feel secure most of the time and the lack of safety is a major concern that triggers us. Therefore, travellers often feel scared of travelling alone or even travelling in groups. The main objective of this product is to provide a solution to solo travellers to prepare themselves if any unwanted scenarios were to happen. It is also to encourage the traveller to travel in less fear. 4 in 1 Safety Kit is a product that comprises safety tools like pepper spray, hand sanitiser, torchlight, and safety alarm. Many self-defence tools promote safety, but most are sold individually according to their purposes. The novelty of the product can be recognized as it provides four different functions of safety packed in one simple product. The idea of innovating this product is to make solo travellers feel safe when travelling alone. We aim to innovate a product that is convenient for people to bring and easy to use. This product is made with a combination of polyvinyl chloride and metal, which can be considered light in terms of weight. The colour of the product is black with a neon colour lining that glow in the dark and comes in a size of 15 centimetres. The uniqueness of this product is it's ecofriendly as it uses high-efficiency solar panels, which can transform solar energy to electric energy that is rechargeable for the safety alarm's speaker and led lights. Also, as for the hand sanitiser and pepper spray, we decided to make it refillable which can save a lot of money.